Prevalence of low lean mass in patients with adult growth hormone deficiency with or without low‐dose growth hormone therapy. (19th March 2019) - Zheng, Xiaoya; Cheng, Qingfeng; Long, Jian; Wang, Yunting; Gong, Lilin; Wei, Qiang; Luo, Rong; Liao, Kun; Ren, Wei
Summary: Objective: The importance of muscle mass has been emphasized in various studies, and growth hormone (GH) deficiency is tightly associated with lean mass loss. Therefore, we aimed to investigate the prevalence of low lean mass in patients with adult growth hormone deficiency (AGHD) who received or did not receive GH therapy. Methods: In this retrospective study, we included patients diagnosed with AGHD by using the insulin tolerance test (ITT) in our hospital. Patients without completed follow‐up data were excluded, and data for 56 patients were analysed. Twenty‐six patients who had received GH therapy for more than 6 months, based on the medical record, were included in the GH group and received recombinant human growth hormone (rhGH) at a dose of 0.5 IU/d. Thirty patients who had not previously received GH treatment were included in the non‐GH group. Many anthropometric and blood biochemical indicators were measured. Body composition was measured on a dual‐energy X‐ray‐absorptiometry (DXA) scanner. Low lean mass was defined as a skeletal muscle index (SMI) <7.0 kg/m 2 in males or 5.7 kg/m 2 in females. Statistical analyses were performed using GraphPad Prism 5.0. Results: Compared to the non‐GH group, the patients who received GH therapy had significantly lower total cholesterol (TC), low‐density lipoprotein cholesterol (LDL‐c) and fasting plasma glucose (FPG). The percentage of patients with low lean mass in GH and non‐GH groups was 30.77% and 60%, respectively. The percentage of total lean was lower in the GH group than in the non‐GH group, but the difference in total lean mass was not statistically significant. Conversely, patients with GH treatment had significantly lower fat mass and percentage than non–GH‐treated patients ( P < 0.05). The GH group had significantly higher serum levels of both IGF‐1 and IGFBP3. Moreover, both IGF‐1 and IGFBP3 were significantly correlated with SMI ( r 2 = 0.275, P = 0.003, and r 2 = 0.138, P = 0.005, respectively). Conclusions: Our data showed that AGHD patients who received low‐dose GH treatment had a lower prevalence of low lean mass than those who did not receive GH treatment. Patients with GH treatment had significantly lower cardiovascular risk factors, especially the lipid profile.